2022
DOI: 10.1136/heartjnl-2021-320116
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and regional differences in practice in a worldwide coronary stent registry

Abstract: ObjectiveThe primary objective was to assess the performance of a new generation thin-strut sirolimus-eluting coronary stent with abluminal biodegradable polymer in an all comer population. The secondary objective was to detail differences in contemporary percutaneous coronary intervention (PCI) practice worldwide.Methodse-Ultimaster was an all-comer, prospective, global registry (NCT02188355) with independent event adjudication enrolling patients undergoing PCI with the study stent. The primary outcome measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
(43 reference statements)
1
8
0
Order By: Relevance
“…Regional subgroup analysis for European, Asian and multicenter trials also showed a nonsignificantly lower risk with the TR approach 13–15 . Most of the studies in our analysis were from European centers where 90% of the CC for any indication is done via a radial approach 68 . There was no statistically significant difference in stroke outcomes in the North American region and this has been iterated in previous studies 19,40 .…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Regional subgroup analysis for European, Asian and multicenter trials also showed a nonsignificantly lower risk with the TR approach 13–15 . Most of the studies in our analysis were from European centers where 90% of the CC for any indication is done via a radial approach 68 . There was no statistically significant difference in stroke outcomes in the North American region and this has been iterated in previous studies 19,40 .…”
Section: Discussionsupporting
confidence: 54%
“…[13][14][15] Most of the studies in our analysis were from European centers where 90% of the CC for any indication is done via a radial approach. 68 There was no statistically significant difference in stroke outcomes in the North American region and this has been iterated in previous studies. 19,40 These results are practically justifiable as there should not be any regional differences in stroke events for either the TR or the TF approach for CC.…”
Section: Discussionmentioning
confidence: 60%
“…The second antiplatelet agent that was added to aspirin was a mix of clopidogrel, prasugrel, and ticagrelor. While these three P2Y 12 inhibitors are commonly used in a similar manner in patients after coronary stenting, [20] the results supporting the author's conclusion are complicated by these mixed agents because the results of platelet-mediated global thrombogenicity comparing between DPI and clopidogrel differ from the comparison of DPI with ticagrelor and prasugrel. Second, all the platelet function assays were conducted in artificial conditions that reduced calcium ion concentration by using a chelator of calcium ions.…”
Section: Dapt To Dpi In Cad Patientsmentioning
confidence: 86%
“…The e-Ultimaster registry is a large, prospective, multicenter, observational study [8] , [9] , [10] . This study was conducted worldwide to evaluate the safety and performance of the Ultimaster drug eluting stent (DES) system (Terumo Corporation, Tokyo, Japan) in an all-comer clinical setting.…”
Section: Methodsmentioning
confidence: 99%